RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI KEUANGAN SEKOLAH BERBASIS WEB PADA SMAN 1 DAWARBLANDONG - Aldi Prasetio; Julianto Lemantara; Edo Yonatan Koentjoro (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
SMAN 1 Dawarblandong is one of the high schools in Mojokerto Regency precisely located at Jl. Yon Djarot Subiyantoro. The common financial administration problems are counterfeiting students ' financial receipts, many mistakes in payment logging, recording mistakes when generating financial statements and making reports too long. The problem causes the inaccuracies in student payment data, the development of the school to slow down and inaccuracies in financial reporting. Based on the above problems, the solutions needed are information systems that can help the school's financial management process, including recording student payments, entry logging, expense recording, financial reports and visualizations Information in the form of school financial dashboards. Based on the results of the evaluation, the application is able to conduct the school's financial records computerized, the process of recap report can be done quickly, the evaluation of school finances can be done by looking at the financial WordPress Display information in real-time.